AN OVERVIEW OF MICROSCOPIC IMAGING TECHNIQUE FOR LUNG CANCER & CLASSIFICATION - Vaishnaw Gorakhnath Kale (International Journal of Innovations in Engineering Research and Technology, 2021)
Lung cancer detection is still a global problem in biomedical field. The rate of lung cancer has been increasing every year. Although there are different techniques which physicians follows such as X-ray, CT, HRCT, PET and MRI, but still thesuccess rate for diseases detection is very less. All though physicians take their decisions by analyzing, visualizing, and comparing the results obtained from all the above mentioned imaging techniques to reach any conclusion, but still the task is very tough one and most of the time physicians experience as well as the medical history of the patient also plays an important role in the whole process. This paper highlights on overview of an electron microscopy lung cancer imaging.